Inconformismo e resistência negra como estratégia de sobrevivência na zona do não-ser : a questão racial no Centro de Atenção Psicossocial, João Pessoa-PB - Monteiro, Vanessa Oliveira (2024)
For more than 300 years a process of enslavement was already underway, even after abolition, the bodies of black people are still destined to overcrowd in hostile environments. When it comes to health and public health, data from the Ministry of Health (MS) infer that the black population is the one that most makes up the Unified Health System (SUS), while at the same time being the most neglected. Madness, the so-called madness, embraced with the eugenics movement in Brazil, found a racist "justification" for cramming black people into asylums, composing, as Lima Barreto said, "a courtyard where black was the most cutting color." In the 70s, this stage of terror was claimed and the Psychiatric Reform (PR) emerged, a struggle that sought the dignity and human rights of people in mental suffering. The Psychosocial Care Center (CAPS) is one of the substitute services where it received people who were deinstitutionalized and those who are now in psychological suffering. That said, the main issue of this study is to discuss racial issues at CAPS III in João Pessoa, Paraíba. How the team understands the demands arising from racism, how racial issues are presented in a so-called and unspoken way, how the "users" perceive and understand the racial discussion within the CAPS. To this end, it is a field research, which had as its reflexive bases authors such as Frantz Fanon, Abdias Nascimento, Neusa Santos, Lélia González, Clóvis Moura, Lima Barreto, Emiliano David, and databases such as BVS, Scielo, Lilacs. As participants, as a team there were 8 professionals, 5 women and 3 men, aged between 25 and 63 years; in self-affirmation regarding color/race, 4 people identified themselves as white, 3 brown and 1 black; While people were monitored in the service, 6 women, aged between 23 and 55 years, in the self-affirmation regarding color/race, 1 of them identified themselves as white, 1 brown, 2 brown, and 2 black. Within the results obtained, it was inferred that the service is submerged in the myth of racial democracy, therefore, it presents itself in a movement of denial of racism, since its effectiveness is identified in the daily life of the CAPS. In addition, it is observed in most of the interviewed team, the delegitimization of the mental health of the black population, as well as being indifferent to the racial discussion, performing, in turn, a process of silencing, negligence, omission and lack of commitment of the service to an equitable, humanized and racialized service. Consequently, the inequities found have been persistent for more than decades and perform the care devices in the city of the colonized. That said, this study is of paramount importance to contribute to the effectiveness of public policies already implemented, such as the National Policy for the Integral Health of the Black Population, as a source for the production of new policies and elaboration of management that account for racial issues and racism within the CAPS, as well as helping the population to observe the racial "subtleties" existing in the SUS.